Effects of Stigma and Discrimination Reduction Trainings Conducted Under the California Mental Health Services Authority An Evaluation of the National Alliance on Mental Illness Adult Programs - Wong, Eunice C. (RAND Corporation, 2015)
This report evaluated three National Alliance on Mental Illness (NAMI) programs aimed at reducing mental illness stigma and discrimination among adult audiences.